Seroprevalence of hepatitis B infection in the Turkish population in Northern Cyprus - Kurugöl, Zafer; Erçal, Hüseyin; Garabli, Hasan; Doğan, Ertan; Bakkaloğlu, Figen; Güllüelli, Emine; Erçal, Gülten; Ozbalikçi, Sonay; Kayimbaşoğlu, Sidika; Ozacar, Tijen; Akşit, Sadik; Koturoğlu, Güldane; et al. (The Turkish Journal of Pediatrics, 2009)
This study was conducted to determine the seroprevalence of hepatitis B virus (HBV) infection in the Turkish population in Northern Cyprus. The secondary aim of this study was to assess the impact of the universal infant hepatitis B vaccination program, which started in 1998. A total of 600 persons 1- to 30-years-old were selected for the study with cluster sampling. The information on sociodemographic characteristics was gathered for each participant and in 585 of them, hepatitis B surface antigen (HBsAg), anti-hepatitis B surface antigen antibody (anti-HBs) and anticore antibody (anti-HBc) were tested. The overall prevalence of anti-HBc and HBsAg carriage was 13.2% and 0.85%, respectively. Old age and low parental educational level were the major independent risk factors for HBV transmission. Seroprevalence of both anti-HBc and anti-HBs antibodies was similar in children 1-7 years of age. After 8 years of age, anti-HBc seroprevalence increased significantly with age, while anti-HBs prevalence decreased (p